Jewish Women, Identity, and the Aufklärung: The German-speaking Enlightenment around 1800 - Josephine Porter (Central Europe)
This paper poses the question, “how enlightened was German-speaking central Europe around 1800?” The initial idea was to explore how marginalized groups accessed the German Enlightenment. During the process of writing, it developed into a wider exploration of female Jewish identity. This revised and lengthened paper, therefore, has become a critical analysis of civil society’s perception of Jewish female participants and their unique identity in nineteenth-century Germany.